1999
DOI: 10.1016/s0928-8244(99)00059-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Candida albicans attachment to extracellular matrix by antibodies which recognize hydrophobic cell wall proteins

Abstract: Cell surface hydrophobicity influences the adhesive properties of the opportunistic fungal pathogen Candida albicans. Hydrophobic proteins are present in the C. albicans cell wall. These proteins were used to generate a polyclonal antiserum and monoclonal antibodies. We characterized three of these monoclonal antibodies (designated 6C5, 5F8 and 5D8) that recognize different hydrophobic cell wall proteins. Initial characterization of the three antigens, and assessment of their distribution among various Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The yeast isolates used in this study are listed in Table 1. Isolates were grown and subsequently subcultured (inoculum concentration of 1 ϫ 10 6 to 3 ϫ 10 6 cells/ml) in Sabouraud dextrose broth (SDB) or phosphate-buffered yeast nitrogen base supplemented with 2% glucose (YNB2G) at 23 or 37°C to stationary phase (26 to 28 h) (29,43). All assays were performed on cells which were harvested from the second subculture (third pass in the indicated medium).…”
Section: Methodsmentioning
confidence: 99%
“…The yeast isolates used in this study are listed in Table 1. Isolates were grown and subsequently subcultured (inoculum concentration of 1 ϫ 10 6 to 3 ϫ 10 6 cells/ml) in Sabouraud dextrose broth (SDB) or phosphate-buffered yeast nitrogen base supplemented with 2% glucose (YNB2G) at 23 or 37°C to stationary phase (26 to 28 h) (29,43). All assays were performed on cells which were harvested from the second subculture (third pass in the indicated medium).…”
Section: Methodsmentioning
confidence: 99%
“…This could be a factor in the high virulence of hydrophobic cells compared to that of hydrophilic cells in mice. MAbs to cell surface hydrophobic protein inhibited the adherence of cells to fibronectin and laminin (237). Pretreatment of hydrophobic cells with MAb also reduced adherence to endothelial cell monolayers (125).…”
Section: Adhesinsmentioning
confidence: 96%
“…The role of antibody immunity in fungal infections remains a controversial subject. Many in vivo or in vitro studies have provided evidence for or against the importance of antibody immunity to C. albicans (Casadevall, 1995 concerned the inhibition of attachment by antibodies that recognize cell-wall proteins (Masuoka et al, 1999;San Millan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that antibody immunity against C. albicans may participate in host defence by preventing attachment (Han & Cutler, 1995 concerned the inhibition of attachment by antibodies that recognize cell-wall proteins (Masuoka et al, 1999;San Millan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation